Analysis of Green Building Certification System for Developing G-SEED: Focusing on the Comparison of LEED and BREEAM. Issue 1 (28th February 2018) - Yun, Yosun; Cho, Dongwoo; Chae, Changu
G-SEED(Green Standard for Energy and Environmental Design) is operating in Korea as a certification system to evaluate the environmental friendliness of buildings. Buildings are generating loads such as carbon dioxide emission, energy consumption, the consumption of resources, destruction of natural ecosystem, change of global climate, pollution of indoor environment, and waste generation. For this purpose, a green building certification system has been introduced. In the green building certification system, evaluation of buildings through methods such as utilization of natural energy, adoption of energy saving system, rainwater management, etc., is induced to reduce environmental load. These certification systems are operated by each country. The level of the certification system is different according to the characteristics such as climate environment. BREEAM in the UK and LEED in the US are operating a version for international certification as well as domestic certification. In this study, analyze the certification system which operates the global version such as BREEAM, LEED. And to investigate the differences between domestic and international versions of each version of the certification system. Certification items classified as reflected by climate characteristics, national characteristics reflected items, general items, such as attempts to analyze the rating system. And certification items were grouped into general "Global certification items" having no specificity for locality and "Local certification items" that differ by each locality according to social, environmental, and political factors. Using the analysis results that comparison of LEED and BREEAM, the study then aims to ascertain the possibility of whether the G-SEED can be used to certify international buildings. And explore the possibility of developing international version of the G-SEED and indicate the direction of G-SEED amendments that may arise in the future. The study results would be available as basic data at the development of G-SEED for international version.